Citoyenneté et réconciliation au Rwanda - Junod, Roland (Collection du centre de recherche sociale, 2015)
This action research jointly undertaken by the Center for Conflict Manage-ment in Butare and the Haute Ecole de Travail Social in Geneva aims at analysing and supporting pilot experiences by community actors in post-genocide Rwanda. Such experiences are analysed through dialogs involving field actors, Rwandan and Swiss researchers. Special attention is paid to managing conflicts related to identity and memory and rebuilding social solidarity among citizens. Expected benefits include training of field actors and those involved in reconciliation work in general.